Legal and regulatory framework for the introduction of Islamic retail-banking products in Canadian banks - Benaziez, Samia (IIUM Institute of Islamic Banking and Finance, International Islamic University Malaysia, 2021)
Islamic finance has made its first steps in Canada; however, there is still a lack of Islamic financial products in the country. The Muslim community still struggles nowadays in finding retail-banking products that do not contravene their religion. In fact, there are some Islamic financial institutions in Canada; however, these face many challenges as to the legal and regulatory framework of the financial system. The literature has proven that for the success of Islamic finance it has to start from the Canadian banks that have full support from the government and a well established and powerful presence in the country; in the current legal and regulatory framework of the Canadian banking system represents an obstacle as to the offering of Islamic retail-banking products in Canadian banks. This research deeply delved in the study of the Canadian legal and regulatory framework and found that there are various issues and challenges faced by Islamic Financial Institutions in Canada as well as different issues and challenges that impede Canadian Banks from offering Islamic Retail-Banking Products. As a result, some amendments need to be made in this framework for the offering of Islamic retail-banking products in Canadian Banks, the most important ones being in the Bank Act as well as some other amendments. These amendments were analyzed in details in this research and it is recommended that Canadian authorities and policy-makers take them into consideration in order to satisfy the needs of the Canadian Muslim Community.